PENGARUH PENGGUNAAN MEDIA FLIPBOOK INTERAKTIF TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 31 PANAIKANG KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Sudarto, Sudarto; M. Ikhsan Sukaria; Faqihudin, Faqihudin (Jurnal Cakrawala Ilmiah, 2025)
This study is a pre-experimental study that aims to determine whether the use of interactive Flipbook media has an effect or not in improving the IPAS learning outcomes of the 5th Grade at SDN 31 Panaikang. The population in this study were all thev 5th Grade students at SDN 31 Panaikang with a sample of 25 students selected using the saturated sampling techniques. The data collection technique used was a test technique with a research instrument in the form of a test sheet. The data analysis used was descriptive and inferential statistical analysis. Based on the results of the descriptive statistical analysis, the average pretest was of 50.96 and the average posttest was of 73.88. The data obtained were then analyzed using a paired sample t-test with a significance level of 0.05. From the results of the data analysis, tcount 12.8809> ttable 2.064, so H0 was rejected and H1 was accepted, which means that there is a significant difference in the learning outcomes of the 5th Grade students at SDN 141 Lilina Ajangale, Bone Regency before and after the use of Interactive Flipbook media. Conclusion: The use of Interactive Flipbook Amedia has a significant effect on improving the IPAS learning outcomes of students of the 5th Grade at SD Negeri 141 Lilina Ajangale, Bone Regency